Connecting ambient toxicity testing with community-level responses of benthic macroinvertebrates in an impacted stream in East Tennessee, USA - Louise M. Stevenson; Paul G. Matson; Peyton C. Marcum; Nikki J. Jones; Scott C. Brooks; Trystan Bordeau; Allison M. Fortner; Natalie A. Griffiths; Christopher R. DeRolph; R. Trent Jett; Michael W. Jones; Peijia Ku; et al. (Journal of Environmental Management, 2026)

Seeds in suspension: Cell type-specific control of seed dormancy and germination initiation - Lim Chee Liew; Lucas Auroux; George W. Bassel; Mathew G. Lewsey (Current Opinion in Plant Biology, 2026)

The potential impact of microplastic contamination in cow manure on maternal dung burying behavior and larval survival in the dung beetle Onthophagus taurus - Nathan J. McConnell; Jaydon Galindo Lovell; Jill Walker; Benjamin J. Mathews; Scott G. Morton; Jonathan B. Shurin; Patrick T. Rohner (Chemosphere, 2026)

Comparing gradient boosting and discrete choice models for urban work-trip mode choice: a case study of Tiruchirappalli, India - S. Anita; Samson Mathew; G. Subbaiyan; B. Janet (Innovative Infrastructure Solutions, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Seasonal distribution of physico-chemical parameters in the tropical mangrove environments of Kerala, Southwest coast of India: a comparative evaluation using statistical approach - Jennees Mathew; Anu Gopinath; G. Anusha (Tropical Ecology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Spatial variability in the carbon stocks of different seagrass meadows of southern Palk Bay, India: Influence of species composition, sediment characteristics and restoration efforts - N. Gladwin Gnana Asir; G. Mathews; K. Diraviya Raj; P. Dinesh Kumar; A. Arasamuthu; R.L. Laju; Bakan Jagdish Sudhakar; J.K. Patterson Edward (Marine Pollution Bulletin, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Guava leaf (Psidium guajava) byproducts in animal and fish diets: a review of health benefits, immunomodulation, and sustainable applications - Khaled M. Al-Marakby; Islam G. Abdelghani; Ehab El-Haroun; Zeinab Mahasneh; Roshmon Thomas Mathew; Asmaa M. Sheiha; Mohamed F. Abo El-Maati; El-Sayed Hemdan Eissa; Md Altafur Rahman; Sameh A. Abdelnour (Tropical Animal Health and Production, 2026)

Systemic Metabolites and Cytokines as Predictive Biomarkers of Metabolic Syndrome in Young Healthy Cohort: A Prospective Study - Reema George; Limi Elizabeth Mathew; Maya G. Pillai; Helen Antony (Indian Journal of Clinical Biochemistry, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Efficacy of an inflow diversion wall for managing eutrophication in two hydrologically connected lakes: A modelling study - Matthew J. Prentice; Mathew G. Allan; Andy Bruere; Deniz Özkundakci (Ecological Engineering, 2026)

Transcranial alternating current stimulation improves ballistic motor performance in trained and untrained limbs of healthy older adults - Nishadi N. Gamage; Wei-Yeh Liao; Philip J. Atherton; Mathew Piasecki; George M. Opie; John G. Semmler (GeroScience, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Effects of polystyrene nanoplastics on the female reproductive system in mice: Implications for ovarian function and follicular development - Mahsa Gholiof; Jocelyn M. Wessels; Warren G. Foster; Victoria Turpin; Mathew Leonardi (Reproductive Toxicology, 2025)

Long term coral restoration efforts to mitigate anthropogenic and climatic impacts in Gulf of Mannar, India: Lessons learnt, success, challenges and prospects - J.K. Patterson Edward; G. Mathews; K. Diraviya Raj; Jamila Patterson; Dan Wilhelmsson; Jagdish Sudhakar Bakan (Journal of Environmental Management, 2025)

Comparison of mangroves and other coastal vegetation in effectively trapping microplastics - Bakan Jagdish Sudhakar; G. Mathew (Estuarine, Coastal and Shelf Science, 2025)

Performance of an oscillatory electrode reactor for electrochemical phosphate removal - Salil S. Mathew; Hassan G. Gomaa; Madhumita B. Ray (Journal of Environmental Chemical Engineering, 2025)

Dynamic and spatial control of cellular activity during seed germination - Mathew G. Lewsey; George W. Bassel; James Whelan (Current Opinion in Plant Biology, 2025)

Combining Observations and Models: A Review of the CARDAMOM Framework for Data‐Constrained Terrestrial Ecosystem Modeling - Matthew A. Worden; T. Eren Bilir; A. Anthony Bloom; Jianing Fang; Lily P. Klinek; Alexandra G. Konings; Paul A. Levine; David T. Milodowski; Gregory R. Quetin; T. Luke Smallman; Yinon M. Bar‐On; Renato K. Braghiere; et al. (Global Change Biology, 2025)
The rapid increase in the volume and variety of terrestrial biosphere observations (i.e., remote sensing data and in situ measurements) offers a unique opportunity to derive ecological insights, refine process‐based models, and improve forecasting for decision support. However, despite their potential, ecological observations have primarily been used to benchmark process‐based models, as many past and current models lack the capability to directly integrate observations and their associated uncertainties for parameterization. In contrast, data assimilation frameworks such as the CARbon DAta MOdel fraMework (CARDAMOM) and its suite of process‐based models, known as the Data Assimilation Linked Ecosystem Carbon Model (DALEC), are specifically designed for model‐data fusion. This review, motivated by a recent CARDAMOM community workshop, examines the development and applications of CARDAMOM, with an emphasis on its role in advancing ecosystem process understanding. CARDAMOM employs a Bayesian approach, using a Markov Chain Monte Carlo algorithm to enable data‐driven calibration of DALEC parameters and initial states (i.e., carbon pool sizes) through observation operators. CARDAMOM's unique ability to retrieve localized model process parameters from diverse datasets—ranging from in situ measurements to global satellite observations—makes it a highly flexible tool for analyzing spatially variable ecosystem responses to environmental change. However, assimilating these data also presents challenges, including data quality issues that propagate into model skill, as well as trade‐offs between model complexity, parameter equifinality, and predictive performance. We discuss potential solutions to these challenges, such as reducing parameter equifinality by incorporating new observations. This review also offers community recommendations for incorporating emerging datasets, integrating machine learning techniques, strengthening collaboration with remote sensing, field, and modeling communities, and expanding CARDAMOM's relevance for localized ecosystem monitoring and decision‐making. CARDAMOM enables a deep, mechanistic understanding of terrestrial ecosystem dynamics that cannot be achieved through empirical analyses of observational datasets or weakly constrained models alone.

Which radionuclides contribute most to seafood ingestion dose? - Mathew P. Johansen; Justin P. Gwynn; Julia G. Carpenter; Sabine Charmasson; Airi Mori; Blake Orr; Marie Simon-Cornu; Iolanda Osvath; Paul Mc Ginnity (Journal of Environmental Radioactivity, 2025)

Patterns and Drivers of Phylogenetic Beta Diversity in the Forests and Savannas of Africa - Mathew Rees; Adeline Fayolle; John L. Godlee; Anais P. Gorel; David J. Harris; Kyle G. Dexter (Journal of Biogeography, 2025)
Aim Studying beta diversity, or the variation in species composition among communities, can give insights into plant community assembly over space and time. If different biomes show contrasting large‐scale beta‐diversity patterns, this can indicate divergent evolutionary histories or ecological processes that then drive species turnover among communities. Here, we examine phylogenetic beta‐diversity patterns across Africa in forest and savanna assemblages, the two most widespread tropical biomes on the continent. We hypothesise that savannas will show lower phylogenetic beta diversity due to their younger evolutionary history. Location Tropical Africa. Taxon Woody angiosperms. Methods We gathered 301,159 occurrences of woody angiosperms representing 1883 forest species and 1302 savanna species. We compared levels of phylogenetic beta diversity between forest and savanna assemblages, analysed spatial patterns of phylogenetic beta diversity using 1° grid cells and modelled their relationship with climate, disturbance and geographical distance. Results We found that savannas show greater relative regional phylogenetic beta diversity, whereas forest assemblages show greater relative local phylogenetic beta diversity. The spatial distribution of beta diversity showed strong East–West patterns for both forests and savannas, aligned with a major floristic discontinuity associated with the Albertine rift. Our results also highlighted West Africa as showing a high amount of compositional change for both biomes, arranged along an aridity gradient. Variance partitioning showed that predictors linked to precipitation were the main drivers of compositional change for both forests and savannas, but the importance of individual predictors was different in each biome. Main Conclusions Contrary to our expectations, our results indicate that savannas may have a deeper and richer evolutionary history than suggested by previous studies and that individual regions of both forest and savanna have high conservation value. Finally, our results demonstrate that environmental filtering is the dominant force influencing the assembly of these two important biomes at a continental spatial scale.

Review of Disruptive Technologies in 3D Bioprinting - Joshua G. Hunsberger; Pearly Pandya; Molly K. Mulligan; Davide Marotta; Lorenzo Moroni; Maxim Shusteff; Grace Brogan; Mathew Brovold; James Yoo; Jacob Koffler; Isac Lazarovits; Salil Desai; et al. (Current Stem Cell Reports, 2025)
Purpose of Review The purpose of this review is to share insights from recognized experts in 3D biopriniting on the recent advances in these technologies discussed during a recent workshop held in conjunction with the 2024 ISS National Laboratory Research and Development Conference (ISSRDC). We seek to answer how microgravity can be used as a disruptor to make further advances not possible through conventional means. Recent Findings This review will cover current efforts underway to use microgravity for 3D bioprinting. For instance multi-levitation biofabrication technology funded under the EU PULSE project is currently being used to create cardiovascular 3D in vitro models to better mimic cardiac and vascular physiology compared to organoids. These types of models could be expanded to other organ systems and disease models to use the environment of microgravity to unlock new signaling pathways to cure disease. Summary The major takeaway from this review is that microgravity will unlock new opportunities for 3D bioprinting that were simply not possible using conventional means. We provide forward looking answers to what microgravity will inspire from advanced biomaterials to new disease models to even creating a knowledge hub for 3D bioprinting to launch new platforms at record speeds.

Next generation Arctic vegetation maps: Aboveground plant biomass and woody dominance mapped at 30 m resolution across the tundra biome - Kathleen M. Orndahl; Logan T. Berner; Matthew J. Macander; Marie F. Arndal; Heather D. Alexander; Elyn R. Humphreys; Michael M. Loranty; Sarah M. Ludwig; Johanna Nyman; Sari Juutinen; Mika Aurela; Juha Mikola; et al. (Remote Sensing of Environment, 2025)

Nutrient Recovery Using Short-Circuited Closed Cycle (SCC) Flow Electrode Capacitive Deionization - Furaha N. Alphonce; Salil Mathew; Hassan G. Gomaa; Madhumita B. Ray (Environmental Processes, 2025)

Bilateral neuromuscular adaptation to acute unilateral resistance exercise in healthy older adults - Nishadi N. Gamage; Abdulmajeed Altheyab; Yuxiao Guo; Bethan E. Phillips; George M. Opie; John G. Semmler; Philip Atherton; Mathew Piasecki (GeroScience, 2025)
Resistance exercise (RE) enhances functionality in older adults and has proven effective as a means of cross-education in scenarios of unilateral disuse. However, the extent to which older adults demonstrate cross-limb transfer at the motor unit (MU) level following a single bout of unilateral RE is unclear. Thirteen healthy older adults (74.9 ± 4.8 years; 5 females) underwent bilateral neuromuscular assessments pre- and post- a single bout of unilateral RE consisting of sets of 12 repetitions of leg extension of the dominant (exercise) leg, at 75% of 1 repetition maximum, performed to failure. Maximum voluntary contraction (MVC) and force steadiness (FS) were measured. Central and peripheral features of individual MU were recorded using high-density surface electromyography and intramuscular electromyography (HDs/iEMG), during contractions normalised to 25% MVC. Following unilateral RE, MVC reduced in exercise (-14.8%, p < 0.001) and control (-6.9%, p = 0.003) legs, with reduced FS performance in the exercise leg compared to the control (p = 0.002). MU firing rate increased during contractions normalised to 25% baseline MVC in the exercised leg ( p < 0.05), with no adaptation in the control leg ( p > 0.05). All iEMG recorded measures of MU potentials remained unchanged in both legs (all p > 0.05). Acute unilateral RE leads to bilateral MVC reduction in older males and females, demonstrating the cross-limb transfer effect. However, adaptation of MU features was only apparent in the exercised limb, and mechanisms underlying the force decline in the non-exercised limb remain uncertain.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Conservation translocation immediately reverses decline in imperiled sage-grouse populations - Mary B. Meyerpeter; Peter S. Coates; Megan C. Milligan; Brian G. Prochazka; Kade D. Lazenby; Steve Abele; John Tull; Katherine Miller; Jesse Kolar; Steven R. Mathews; David K. Dahlgren; David J. Delehanty (Biological Conservation, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Chandra’s surface thermophysical experiment (ChaSTE) onboard Chandrayaan 3 Lander - Nizy Mathew; K. Durga Prasad; Dinakar Prasad Vajja; V. Aasik; Fazil Mohammad; P.P. Pramod; M. Satheesh Chandran; Kiran John Antony; M. Ram Prabhu; M.B. Dhanya; Manu V. Unnithan; Shiju G. Thomas; et al. (Advances in Space Research, 2025)

Radiological dose from seafood ingestion; a global summary from 40 years of study - Mathew P. Johansen; Justin P. Gwynn; Julia G. Carpenter; Sabine Charmasson; Paul Mc Ginnity; Airi Mori; Blake Orr; Marie Simon-Cornu; Iolanda Osvath (Critical Reviews in Environmental Science and Technology, 2025)

Contaminated oily wastewater treatment using composite membrane adsorption reactor - Hassan G. Gomaa; Wen Zhou; Salil Mathew; Jesse Zhu (Environmental Science and Pollution Research, 2025)

Textural characteristics of channel bed sediments and heavy minerals of the Cauvery River, Southern India: implications on depositional environments, provenance, tectonics and climate - M. Ramkumar; AL Fathima; G. Sugavanam; B. Velliyangiri; M. Selvakumar; S. Anbarasan; M. Sowmiya; S. Kiruthika; K. Balasubramani; V. Thirukumaran; P. D. Roy; R. Nagarajan; et al. (Journal of Sedimentary Environments, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Analysis of biokinetic parameters reveals patterns in mercury accumulation across aquatic species - Louise M. Stevenson; Paul G. Matson; Rachel M. Pilla; Simon Pouil; Tom J. Geeza; Amber Hills; Zapporah Ellis; Sydney Smith; Teresa J. Mathews (Science of The Total Environment, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Biofilm inactivation using LED systems emitting germicidal UV and antimicrobial blue light - Dana Pousty; Ben Ma; Christian Mathews; Manohara Halanur; Hadas Mamane; Karl G. Linden (Water Research, 2024)

Antifibrotic effect of silymarin on arecoline-induced fibrosis in primary human buccal fibroblasts: an in silico and in vitro analysis - Divyambika Catakapatri Venugopal; Paramesh Viswanathan; Soundharya Ravindran; Alan Mathew Punnoose; Madhavan Yasasve; Davis G. Dicky John; Lavanya Prabhakar; Gnanasambandan Ramanathan; Sathasivasubramanian Sankarapandian; Vijayalakshmi Ramshankar (Molecular Biology Reports, 2024)

Wastewater-based surveillance of SARS-CoV-2: Short-term projection (forecasting), smoothing and outlier identification using Bayesian smoothing - Douglas G. Manuel; Gauri Saran; Ivan Lee; Warsame Yusuf; Mathew Thomson; Élisabeth Mercier; Vince Pileggi; R. Michael McKay; Ryland Corchis-Scott; Qiudi Geng; Mark Servos; Heather Ikert; et al. (Science of The Total Environment, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Extreme iron cycling in a coastal lake-lagoon system driven by interactions between climate and entrance management - Scott G. Johnston; Thor Aaso; Damien T. Maher; Edward D. Burton; Mitchell Call; Mathew Birch; John Schmidt; Angus Ferguson (Science of The Total Environment, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Biometeorological analysis on the molecular incidence of babesiosis and ehrlichiosis in dogs - Y. Ajith; Sasi Adithya; Varuna P. Panicker; N. Athira; V. Beena; M. Saifudeen Safeer; P. Preena; A. R. Nisha; C. Divya; S. G. Sangeetha; C. G. Umesh; R. C. Sundararajan; et al. (Theoretical and Applied Climatology, 2024)

Remedial effectiveness of a pond biomanipulation: Habitat value and concentrations of polychlorinated biphenyls in fish - Rebecca A. Efroymson; Mark J. Peterson; R. Trent Jett; Natalie A. Griffiths; Evin T. Carter; Allison M. Fortner; Christopher R. DeRolph; Peijia Ku; Paul G. Matson; Rachel M. Pilla; Teresa J. Mathews (Journal of Hazardous Materials, 2024)

Seafood dose parameters: Updating 210Po retention factors for cooking, decay loss and mariculture - Mathew P. Johansen; Julia G. Carpenter; Sabine Charmasson; Justin P. Gwynn; Paul Mc Ginnity; Airi Mori; Blake Orr; Marie Simon-Cornu; Iolanda Osvath (Journal of Environmental Radioactivity, 2023)

Vascular senescence and leak are features of the early breakdown of the blood–brain barrier in Alzheimer’s disease models - Ka Ka Ting; Paul Coleman; Hani Jieun Kim; Yang Zhao; Jocelyne Mulangala; Ngan Ching Cheng; Wan Li; Dilini Gunatilake; Daniel M. Johnstone; Lipin Loo; G. Gregory Neely; Pengyi Yang; et al. (GeroScience, 2023)
Alzheimer’s disease (AD) is an age-related disease, with loss of integrity of the blood–brain barrier (BBB) being an early feature. Cellular senescence is one of the reported nine hallmarks of aging. Here, we show for the first time the presence of senescent cells in the vasculature in AD patients and mouse models of AD. Senescent endothelial cells and pericytes are present in APP/PS1 transgenic mice but not in wild-type littermates at the time of amyloid deposition. In vitro, senescent endothelial cells display altered VE-cadherin expression and loss of cell junction formation and increased permeability. Consistent with this, senescent endothelial cells in APP/PS1 mice are present at areas of vascular leak that have decreased claudin-5 and VE-cadherin expression confirming BBB breakdown. Furthermore, single cell sequencing of endothelial cells from APP/PS1 transgenic mice confirms that adhesion molecule pathways are among the most highly altered pathways in these cells. At the pre-plaque stage, the vasculature shows significant signs of breakdown, with a general loss of VE-cadherin, leakage within the microcirculation, and obvious pericyte perturbation. Although senescent vascular cells were not directly observed at sites of vascular leak, senescent cells were close to the leak area. Thus, we would suggest in AD that there is a progressive induction of senescence in constituents of the neurovascular unit contributing to an increasing loss of vascular integrity. Targeting the vasculature early in AD, either with senolytics or with drugs that improve the integrity of the BBB may be valid therapeutic strategies.

Revelations on photosystem II, thermoluminescence, and artificial photosynthesis: a retrospective of Govindjee from fundamentals to applications - Mathew Veena; P. P. Sameena; Nair G. Sarath; Louis Noble; K. P. Raj Aswathi; M. S. Amritha; Riya Johnson; Joy M. Joel; K. S. Anjitha; Harvey J. M. Hou; Jos T. Puthur (Physiology and Molecular Biology of Plants, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Genome‐wide variant analyses reveal new patterns of admixture and population structure in Australian dingoes - Kylie M. Cairns; Mathew S. Crowther; Heidi G. Parker; Elaine A. Ostrander; Mike Letnic (Molecular Ecology, 2023)
Admixture between species is a cause for concern in wildlife management. Canids are particularly vulnerable to interspecific hybridisation, and genetic admixture has shaped their evolutionary history. Microsatellite DNA testing, relying on a small number of genetic markers and geographically restricted reference populations, has identified extensive domestic dog admixture in Australian dingoes and driven conservation management policy. But there exists a concern that geographic variation in dingo genotypes could confound ancestry analyses that use a small number of genetic markers. Here, we apply genome‐wide single‐nucleotide polymorphism (SNP) genotyping to a set of 402 wild and captive dingoes collected from across Australia and then carry out comparisons to domestic dogs. We then perform ancestry modelling and biogeographic analyses to characterise population structure in dingoes and investigate the extent of admixture between dingoes and dogs in different regions of the continent. We show that there are at least five distinct dingo populations across Australia. We observed limited evidence of dog admixture in wild dingoes. Our work challenges previous reports regarding the occurrence and extent of dog admixture in dingoes, as our ancestry analyses show that previous assessments severely overestimate the degree of domestic dog admixture in dingo populations, particularly in south‐eastern Australia. These findings strongly support the use of genome‐wide SNP genotyping as a refined method for wildlife managers and policymakers to assess and inform dingo management policy and legislation moving forwards.

Characterization of Enterocytozoon hepatopenaei causing hepatopancreatic microsporidiosis in L. vannamei and a new molecular method for its detection in shrimps, and other environmental samples - Mithun Raj; G. Sathiyaraj; Biju Narayanan; B. Babu; Mathews Varkey; K. Karthickkannan; R. Ganeshamurthy; Anup Mandal; S. Kandan (Journal of Invertebrate Pathology, 2023)

Advances in pursuit of fluorine in the interstellar medium and beyond: relevance to its terrestrial chemistry - Thomas Mathew; Socrates B. Munoz; Olivier Forni; Alain Tressaud; G. K. Surya Prakash (Journal of Fluorine Chemistry, 2023)

The enduring Ediacaran paleomagnetic enigma - Mathew Domeier; Boris Robert; Joseph G. Meert; Evgeniy V. Kulakov; Phil J.A. McCausland; Ricardo I.F. Trindade; Trond H. Torsvik (Earth-Science Reviews, 2023)

Growth conditions impact particulate absorption and pigment concentrations in two common bloom forming cyanobacterial species - Laura T. Kelly; Lisa Reed; Jonathan Puddick; Ian Hawes; Brendan J. Hicks; Mathew G. Allan; Moritz K. Lehmann; Susanna A. Wood (Harmful Algae, 2023)

Characterizing near-surface salinity variability in the northern Bay of Bengal and its potential drivers during extreme freshening years of the 2011–2019 period - C. Anoopa Prasad; K. Jossia Joseph; K.N. Navaneeth; Martin V. Mathew; Fabrice Papa; B. Rohith; R. Venkatesan; G. Latha (Dynamics of Atmospheres and Oceans, 2023)

A solar radiation and biosand filtration system for cooking and water treatment - H. Shollenberger; G. Mathews; M. Young; S. Clark; Y. Chen (International Journal of Environmental Science and Technology, 2023)

Use of phospholipid fatty acid analysis as phenotypic biomarkers for soil health and the influence of management practices - Charlotte E. Norris; Mathew J.B. Swallow; Daniel Liptzin; Michael Cope; G. Mac Bean; Shannon B. Cappellazzi; Kelsey L.H. Greub; Elizabeth L. Rieke; Paul W. Tracy; Cristine L.S. Morgan; C. Wayne Honeycutt (Applied Soil Ecology, 2023)

Geothermal energy production adversely affects a sensitive indicator species within sagebrush ecosystems in western North America - Peter S. Coates; Brian G. Prochazka; Shawn T. O'Neil; Sarah C. Webster; Shawn Espinosa; Mark A. Ricca; Steven R. Mathews; Michael Casazza; David J. Delehanty (Biological Conservation, 2023)

Global net biome CO 2 exchange predicted comparably well using parameter–environment relationships and plant functional types - Caroline A. Famiglietti; Matthew Worden; Gregory R. Quetin; T. Luke Smallman; Uma Dayal; A. Anthony Bloom; Mathew Williams; Alexandra G. Konings (Global Change Biology, 2023)
Accurate estimation and forecasts of net biome CO 2 exchange (NBE) are vital for understanding the role of terrestrial ecosystems in a changing climate. Prior efforts to improve NBE predictions have predominantly focused on increasing models' structural realism (and thus complexity), but parametric error and uncertainty are also key determinants of model skill. Here, we investigate how different parameterization assumptions propagate into NBE prediction errors across the globe, pitting the traditional plant functional type (PFT)‐based approach against a novel top‐down, machine learning‐based “environmental filtering” (EF) approach. To do so, we simulate these contrasting methods for parameter assignment within a flexible model–data fusion framework of the terrestrial carbon cycle (CARDAMOM) at a global scale. In the PFT‐based approach, model parameters from a small number of select locations are applied uniformly within regions sharing similar land cover characteristics. In the EF‐based approach, a pixel's parameters are predicted based on underlying relationships with climate, soil, and canopy properties. To isolate the role of parametric from structural uncertainty in our analysis, we benchmark the resulting PFT‐based and EF‐based NBE predictions with estimates from CARDAMOM's Bayesian optimization approach (whereby “true” parameters consistent with a suite of data constraints are retrieved on a pixel‐by‐pixel basis). When considering the mean absolute error of NBE predictions across time, we find that the EF‐based approach matches or outperforms the PFT‐based approach at 55% of pixels—a narrow majority. However, NBE estimates from the EF‐based approach are susceptible to compensation between errors in component flux predictions and predicted parameters can align poorly with the assumed “true” values. Overall, though, the EF‐based approach is comparable to conventional approaches and merits further investigation to better understand and resolve these limitations. This work provides insight into the relationship between terrestrial biosphere model performance and parametric uncertainty, informing efforts to improve model parameterization via PFT‐free and trait‐based approaches.

Natural organic matter flocculation behavior controls lead phosphate particle aggregation by mono- and divalent cations - Juntao Zhao; Riya A. Mathew; David S. Yang; Peter G. Vekilov; Yandi Hu; Stacey M. Louie (Science of The Total Environment, 2023)

Development of SpCas9-expressing bovine mammary epithelial cell lines - Alexander J. Trevarton; Emily R. Mears; Janelle Moody; Thomas J. Lopdell; Thaize Q. Chometon; John A. Taylor; Carol J. Wang; Mathew D. Littlejohn; Russell G. Snell (In Vitro Cellular & Developmental Biology - Animal, 2023)

Probing the influence of liquid nitrogen assisted chemical reduction on the nature of passivation layer, magnetic properties, and Cr (VI) remediation performance of nanoscale zero valent iron - Nibin K. Mathew; Rohith Vinod K; Theertharaman G; M. Navaneethan; S. Balakumar (Journal of Environmental Chemical Engineering, 2023)

Effects of radiation exposure on brain health: a state of the art and new challenges - Jayalakshmi Jayan; Harsha Roshi; Fathima Farzana Perumbilly Ashraf; Parvathy G. Nair; Aparna Vijayakumar; Aathira Sujathan Nair; Leena K. Pappachen; Mohamed A. Abdelgawad; Della Grace Thomas Parambi; Lotfi Aleya; Bijo Mathew (Environmental Science and Pollution Research, 2022)

An unprecedented function for a tungsten-containing oxidoreductase - Liju G. Mathew; Dominik K. Haja; Clayton Pritchett; Winston McCormick; Robbie Zeineddine; Leo S. Fontenot; Mario E. Rivera; John Glushka; Michael W. W. Adams; William N. Lanzilotta (JBIC Journal of Biological Inorganic Chemistry, 2022)

Production Optimization and In Vitro Evaluation of Anti-proliferative, Anti-oxidant and Anti-inflammatory Potential of the Antibacterial Peptide MFAP9 - Rekha Mol Kollakalnaduvil Raghavan; Manzur Ali Pannippara; Sapna Kesav; Abraham Mathew; Sarita G. Bhat; C. M. Rafeeq; K. K. Elyas (International Journal of Peptide Research and Therapeutics, 2022)

Phlorotannins–bioactivity and extraction perspectives - Lekshmi R. G. Kumar; Preethy Treesa Paul; K. K. Anas; C. S. Tejpal; N. S. Chatterjee; T. K. Anupama; Suseela Mathew; C. N. Ravishankar (Journal of Applied Phycology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Critical role of nitric oxide in impeding COVID-19 transmission and prevention: a promising possibility - Rajalakshmi Rajendran; Anjana Chathambath; Abdullah G. Al-Sehemi; Mehboobali Pannipara; Mazhuvancherry Kesavan Unnikrishnan; Lotfi Aleya; Roshni Pushpa Raghavan; Bijo Mathew (Environmental Science and Pollution Research, 2022)

Internal seiches as drivers of fish depth use in lakes - Jill L. Brooks; Jonathan D. Midwood; Adam Smith; Steven J. Cooke; Bryan Flood; Christine M. Boston; Patricia Semecsen; Susan E. Doka; Mathew G. Wells (Limnology and Oceanography, 2022)
Inland temperate lakes undergo various physical processes, such as thermal stratification, that dictate the spatial availability of suitable temperature and dissolved oxygen conditions. Here, we use intensive limnological monitoring and acoustic telemetry transmitters implanted in wild fish to document the magnitude and frequency of thermocline deflection events (i.e., wind driven internal seiches that lead to upwelling of hypoxic hypolimnetic water) and their influence on freshwater fish depth use in a coastal embayment of Lake Ontario. The embayment experienced around 100 internal seiche events during a 3‐month period and tracking of walleye ( Stizostedion vitreus ) vertical positions in the water column showed clear trends of avoidance of low dissolved oxygen. Quantile regression showed a significant correlation between walleye vertical position and the depth of the 3, 4, and 5 mg L −1 oxyclines, with the 3 mg L −1 oxycline having the largest effect. Upwellings of the hypoxic hypolimnion forced walleye to use the water column above these fluctuating oxyclines (5 th percentile, p −1 oxycline. Understanding how fish respond to upwelling events (both temperature and oxygen) is important for fisheries assessment, management, and habitat restoration planning as there is clear avoidance of suboptimal oxygen conditions and sampling in the overcrowded fringes of these low‐oxygen zones could artificially inflate population estimates.

Current understandings and perspectives of petroleum hydrocarbons in Alzheimer’s disease and Parkinson’s disease: a global concern - Rajalakshmi Rajendran; Roshni Pushpa Ragavan; Abdullah G. Al-Sehemi; Md. Sahab Uddin; Lotfi Aleya; Bijo Mathew (Environmental Science and Pollution Research, 2022)

Correction to: A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)

A Standards Organization for Open and FAIR Neuroscience: the International Neuroinformatics Coordinating Facility - Mathew Birdsall Abrams; Jan G. Bjaalie; Samir Das; Gary F. Egan; Satrajit S. Ghosh; Wojtek J. Goscinski; Jeffrey S. Grethe; Jeanette Hellgren Kotaleski; Eric Tatt Wei Ho; David N. Kennedy; Linda J. Lanyon; Trygve B. Leergaard; et al. (Neuroinformatics, 2022)
There is great need for coordination around standards and best practices in neuroscience to support efforts to make neuroscience a data-centric discipline. Major brain initiatives launched around the world are poised to generate huge stores of neuroscience data. At the same time, neuroscience, like many domains in biomedicine, is confronting the issues of transparency, rigor, and reproducibility. Widely used, validated standards and best practices are key to addressing the challenges in both big and small data science, as they are essential for integrating diverse data and for developing a robust, effective, and sustainable infrastructure to support open and reproducible neuroscience. However, developing community standards and gaining their adoption is difficult. The current landscape is characterized both by a lack of robust, validated standards and a plethora of overlapping, underdeveloped, untested and underutilized standards and best practices. The International Neuroinformatics Coordinating Facility (INCF), an independent organization dedicated to promoting data sharing through the coordination of infrastructure and standards, has recently implemented a formal procedure for evaluating and endorsing community standards and best practices in support of the FAIR principles. By formally serving as a standards organization dedicated to open and FAIR neuroscience, INCF helps evaluate, promulgate, and coordinate standards and best practices across neuroscience. Here, we provide an overview of the process and discuss how neuroscience can benefit from having a dedicated standards body.

Correction to: Opportunistic spongivore fishes in a reef of Gulf of Mannar, India - Jonathan Samuel Emmett; K. Diraviya Raj; G. Mathews; R. L. Laju (Environmental Biology of Fishes, 2021)

Opportunistic spongivore fishes in a reef of Gulf of Mannar, India - Jonathan Samuel Emmett; K. Diraviya Raj; G. Mathews; R. L. Laju (Environmental Biology of Fishes, 2021)

Landscape genomics and selection signatures of local adaptation of Eritrean indigenous cattle along environmental gradients - S. Goitom; Mathew G. Gicheha; Francis K. Njonge; Ngeno Kiplangat (Tropical Animal Health and Production, 2021)

Flood impact assessment using field investigations and post-flood survey - Aleena Elsa Mathew; S Sujith Kumar; G Vivek; M Iyyappan; R Karthikaa; P Dinesh Kumar; S K Dash; G Gopinath; Tune Usha (Journal of Earth System Science, 2021)

Growth, mortality, exploitation rate and recruitment pattern of Octopus cyanea (Mollusca: Cephalopoda) in the WIO region: A case study from the Mafia Archipelago, Tanzania - Mathew O. Silas; Mary A. Kishe; Johnson G. Mshana; Masumbuko L. Semba; Said S. Mgeleka; Bigeyo N. Kuboja; Benjamin P. Ngatunga; Muhaji A. Chande; Patroba Matiku (Western Indian Ocean Journal of Marine Science, 2021)
Octopus cyanea is a commercially important cephalopod in the Western Indian Ocean (WIO) region, but scientific information to inform management strategies for the species is limited. A study was conducted in 2014, 2015, 2017 and 2018 to investigate biological parameters including growth, mortality, exploitation rates and recruitment patterns in the sea around Mafia Archipelago, Tanzania. Virtual population analysis (VPA) indicated differential mortality between two sampling sites; the lowest and highest fishing mortality of F = 1.5yr-1 and F = 2.7yr-1 were observed in Bwejuu (Dorsal mantle length, DMT = 18-20 cm) and Jibondo (DMT = 8-12 cm) fishing villages, respectively. The maximum exploitation rate (Emax), which gives the maximum relative yield per recruit, was estimated at 0.380 and 0.379 for Jibondo and Bwejuu, respectively. The exploitation rates E 0.5, which corresponded to 50% of the unexploited stock relative biomass per recruit, were estimated at 0.248 for Jibondo and 0.247 for Bwejuu. These values differ greatly from the exploitation rates of 0.53 and 0.41 for Jibondo and Bwejuu, respectively, suggesting that the stock of O. cyanea is probably being overfished both in terms of yield per recruit and biomass per recruit. The stock-recruit pattern was observed to be continuous year-round, with the peak being between May and July. Since the peak in recruitment of both areas coincides with the south-east monsoon (SE Monsoon) and the level of maximum sustainable yield has been overshot, it is recommended that management plans are implemented that will reduce effort while increasing biomass, for example, implementing temporal octopus fishery closures at a village level.

Coral reef resilience differs among islands within the Gulf of Mannar, southeast India, following successive coral bleaching events - K. Diraviya Raj; Greta S. Aeby; G. Mathews; Gareth J. Williams; Jamie M. Caldwell; R. L. Laju; M. Selva Bharath; P. Dinesh Kumar; A. Arasamuthu; N. Gladwin Gnana Asir; Lisa M. Wedding; Andrew J. Davies; et al. (Coral Reefs, 2021)

Latent heat flux variation during the warming phase of intraseasonal oscillations over northern Bay of Bengal - Simi Mathew; G Latha; R Venkatesan (Journal of Earth System Science, 2020)

Mixing, stratification, and plankton under lake‐ice during winter in a large lake: Implications for spring dissolved oxygen levels - Bernard Yang; Mathew G. Wells; Jingzhi Li; Joelle Young (Limnology and Oceanography, 2020)
The mixing and stratification present under ice‐covered lakes during winter can potentially influence the oxygen concentrations in the subsequent spring. During winter, plankton rely on updrafts caused by convection to remain in the photic zone and perform primary production. Thus, there is a crucial link in winter between under‐ice light levels, circulation, and dissolved oxygen (DO) production. Detailed observations of temperature, oxygen, and incoming solar radiation over three winters between 2015 and 2017 suggested that plankton abundance and DO concentrations were maximal near the end of the winter before the ice melted when there was increased under‐ice light and convection. DO was supersaturated by the end of the severe winter of 2015 when the ice cover duration was the longest. In comparison, DO increased but was not saturated in the warmer winters of 2016 and 2017. The spring overturn started when the water column became isothermal and continued until when the mean water column temperature first exceeded 4°C, at which time, hypolimnetic DO depletion started and continued until the fall overturn. The concentration of DO when the water column becomes stratified in spring, along with the timing of the end of spring overturn, are both important initial conditions for summer DO concentrations.

Eroding islands of Gulf of Mannar, Southeast India: a consequence of long-term impact of coral mining and climate change - N. Gladwin Gnana Asir; P. Dinesh Kumar; A. Arasamuthu; G. Mathews; K. Diraviya Raj; T. K. Ashok Kumar; Deepak S. Bilgi; J. K. Patterson Edward (Natural Hazards, 2020)

Mixing data for multivariate statistical study of groundwater quality - P. G. Dileep Kumar; Narayanan C. Viswanath; Sobha Cyrus; Benny Mathews Abraham (Environmental Monitoring and Assessment, 2020)

Considerations for Soluble Protein Biomarker Blood Sample Matrix Selection - Joel A. Mathews; Yan G. Ni; Connie Wang; Jon E. Peterson; Chad Ray; Xuemei Zhao; Daoyu Duan; Sara Hamon; John Allinson; Martha Hokom; Greta Wegner (The AAPS Journal, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Expanding Tara Oceans Protocols for Underway, Ecosystemic Sampling of the Ocean-Atmosphere Interface During Tara Pacific Expedition (2016–2018) - Gabriel Gorsky; Guillaume Bourdin; Fabien Lombard; Maria Luiza Pedrotti; Samuel Audrain; Nicolas Bin; Emmanuel Boss; Chris Bowler; Nicolas Cassar; Loic Caudan; Genevieve Chabot; Natalie R. Cohen; et al. (Frontiers in Marine Science, 2019)

Melatonin in Alzheimer’s Disease: A Latent Endogenous Regulator of Neurogenesis to Mitigate Alzheimer’s Neuropathology - Md. Farhad Hossain; Md. Sahab Uddin; G. M. Sala Uddin; Dewan Md. Sumsuzzman; Md. Siddiqul Islam; George E. Barreto; Bijo Mathew; Ghulam Md Ashraf (Molecular Neurobiology, 2019)

Regional trends in remotely sensed water clarity over 18 years in the Rotorua Lakes, New Zealand - Moritz K. Lehmann; Uyen Nguyen; Kohji Muraoka; Mathew G. Allan (New Zealand Journal of Marine and Freshwater Research, 2019)
Observations by satellite sensors provide data on inland water systems at spatial and temporal coverage superior to current monitoring programmes. We derived an empirical relationship for Secchi depth using in situ data from eight lakes and data from the Landsat 5 Thematic Mapper, Landsat 7 Enhanced Thematic Mapper Plus and Landsat 8 Operational Land Imager between 1999 and 2018 in the Rotorua Lakes Region in New Zealand. This relationship was then applied to all Landsat data of 23 lakes in that region. A trend analysis on annual and summertime averages of Secchi depth revealed several statistically significant and positive trends, indicating improving water clarity. Our trends were in agreement with those based on in situ observations illustrating the opportunities of remote sensing time series data for lake monitoring and management.

Seagrass restoration in Gulf of Mannar, Tamil Nadu, Southeast India: a viable management tool - J. K. Patterson Edward; K. Diraviya Raj; G. Mathews; P. Dinesh Kumar; A. Arasamuthu; Nisha D’ Souza; Deepak S. Bilgi (Environmental Monitoring and Assessment, 2019)

Future Directions in the Research and Management of Marine Snakes - Vinay Udyawer; Peter Barnes; Xavier Bonnet; François Brischoux; Jenna M. Crowe-Riddell; Blanche D’Anastasi; Bryan G. Fry; Amber Gillett; Claire Goiran; Michael L. Guinea; Harold Heatwole; Michelle R. Heupel; et al. (Frontiers in Marine Science, 2018)

Increased Soil Frost Versus Summer Drought as Drivers of Plant Biomass Responses to Reduced Precipitation: Results from a Globally Coordinated Field Experiment - Hugh A. L. Henry; Mehdi Abedi; Concepción L. Alados; Karen H. Beard; Lauchlan H. Fraser; Anke Jentsch; Juergen Kreyling; Andrew Kulmatiski; Eric G. Lamb; Wei Sun; Mathew R. Vankoughnett; Susanna Venn; et al. (Ecosystems, 2018)

Development of CGMS system in ridge gourd [Luffa acutangula (Roxb.) L.] for production of F1 hybrids - T. Pradeepkumar; J. S. Minimol; Deepu Mathew; K. Veni; C. Varun Roch; P. G. Chithira; Rajeshwary Unni (Euphytica, 2018)

Cenozoic conifer wood from the Gore Lignite Measures, Southland, New Zealand - Mathew R. Vanner; John G. Conran; Jennifer M. Bannister; Daphne E. Lee (New Zealand Journal of Botany, 2018)
Well preserved fossil wood in the form of tree stumps, logs, branches, roots and occasionally bark is common throughout the Gore Lignite Measures, southern New Zealand. The main objective of the present study is to identify the range of forest trees present using anatomical features such as: distinct growth rings; presence or absence of axial parenchyma; uniseriate to triseriate, opposite to alternate, separate or contiguous tracheid pitting; and taxodioid, cupressoid and araucarioid cross‐field pitting. Specimens of silicified and lignified wood are described and illustrated from four localities within the Late Oligocene–Early Miocene Gore Lignite Measures, Southland: Newvale Coal Mine; Mataura Coal Mine; Cosy Dell Coal Pit; and Bennett's Pit. The fossil wood specimens include examples of Araucariaceae, Cupressaceae and Podocarpaceae. Three specimens from Newvale Mine resemble Araucariaceae, while one is assigned to Cupressaceae. Cosy Dell Coal Pit preserved branches of Podocarpaceae . Large stumps and branches preserved at the Mataura Coal Mine are identified as Cupressaceae and Podocarpaceae . Wood recovered from Bennett's Pit resembles either Cupressaceae or Podocarpaceae. Araucariaceae, in the form of Agathis Salisb . trees are today restricted to the northern North Island. Cupressaceae and Podocarpaceae are still extant in modern forests throughout New Zealand. So far, no angiosperm wood has been recognised from the lignite deposits. The forests in which these trees lived were in or near oligotrophic swamps on a deltaic plain. Identification of samples of fossil wood provides new data that can be used to reconstruct the forest vegetation of the Gore Lignite Measures.

Genetic structure and diversity of a rare woodland bat, Myotis bechsteinii: comparison of continental Europe and Britain - Patrick G. R. Wright; Patrick B. Hamilton; Henry Schofield; Anita Glover; Christopher Damant; Ian Davidson-Watts; Fiona Mathews (Conservation Genetics, 2018)

Exploring ethyl methanesulfonate (EMS) treated cotton (Gossypium hirsutum L.) to improve drought tolerance - Travis W. Witt; Mauricio Ulloa; Mathew G. Pelletier; Venugopal Mendu; Glen L. Ritchie (Euphytica, 2018)

Aboveground Carbon Storage and Its Links to Stand Structure, Tree Diversity and Floristic Composition in South-Eastern Tanzania - Iain M. McNicol; Casey M. Ryan; Kyle G. Dexter; Stephen M. J. Ball; Mathew Williams (Ecosystems, 2018)

Managing conflict between large carnivores and livestock - Lily M. van Eeden; Mathew S. Crowther; Chris R. Dickman; David W. Macdonald; William J. Ripple; Euan G. Ritchie; Thomas M. Newsome (Conservation Biology, 2018)
Large carnivores are persecuted globally because they threaten human industries and livelihoods. How this conflict is managed has consequences for the conservation of large carnivores and biodiversity more broadly. Mitigating human–predator conflict should be evidence‐based and accommodate people's values while protecting carnivores. Despite much research into human and large‐carnivore coexistence strategies, there have been few attempts to document the success of conflict‐mitigation strategies on a global scale. We conducted a meta‐analysis of global research on conflict mitigation related to large carnivores and humans. We focused on conflicts that arise from the threat large carnivores pose to livestock. We first used structured and unstructured searching to identify replicated studies that used before–after or control–impact design to measure change in livestock loss as a result of implementing a management intervention. We then extracted relevant data from these studies to calculate an overall effect size for each intervention type. Research effort and focus varied among continents and aligned with the histories and cultures that shaped livestock production and attitudes toward carnivores. Livestock guardian animals most effectively reduced livestock losses. Lethal control was the second most effective control, although its success varied the most, and guardian animals and lethal control did not differ significantly. Financial incentives have promoted tolerance of large carnivores in some settings and reduced retaliatory killings. We suggest coexistence strategies be location‐specific, incorporate cultural values and environmental conditions, and be designed such that return on financial investment can be evaluated. Improved monitoring of mitigation measures is urgently required to promote effective evidence‐based policy.

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Evaluating a polyculture trap crop for organic management of Halyomorpha halys and native stink bugs in peppers - Clarissa R. Mathews; Brett Blaauw; Galen Dively; James Kotcon; Jennifer Moore; Emily Ogburn; Douglas G. Pfeiffer; Taliaferro Trope; James F. Walgenbach; Celeste Welty; Gladis Zinati; Anne L. Nielsen (Journal of Pest Science, 2017)

Association of SNP variants of MHC Class II DRB gene with thermo-physiological traits in tropical goats - Abdulmojeed Yakubu; Adebowale E. Salako; Marcos De Donato; Sunday O. Peters; Michael I. Takeet; Mathew Wheto; Moses Okpeku; Ikhide G. Imumorin (Tropical Animal Health and Production, 2017)

Telemetry-Determined Habitat Use Informs Multi-Species Habitat Management in an Urban Harbour - Andrew M. Rous; Jonathon D. Midwood; Lee F.G. Gutowsky; Nicolas W.R. Lapointe; Rick Portiss; Thomas Sciscione; Mathew G. Wells; Susan E. Doka; Steven J. Cooke (Environmental Management, 2017)

Phylogeny of Trypanosoma brucei and Trypanosoma evansi in naturally infected cattle in Nigeria by analysis of repetitive and ribosomal DNA sequences - Michael I. Takeet; Sunday O. Peters; Benjamin O. Fagbemi; Marcos De Donato; Vivian O. Takeet; Mathew Wheto; Ikhide G. Imumorin (Tropical Animal Health and Production, 2016)

Role of Red-Ant, Oecophylla smaragdina Fabricius (Formicidae: Hymenoptera) in Managing Tea Mosquito Bug, Helopeltis species (Miridae: Hemiptera) in Cashew - G. K. Mahapatro; Jose Mathew (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Comparative Evaluation of Natural Antioxidant Coating and Vacuum-Packaging Technique on Quality Characteristics of Chill Stored Giant Trevally Fillets - P. K. Binsi; C. N. Ravishankar; S. Suseela Mathew; V. P. Athira; K. B. Biji; C. G. Joshy; T. K. Srinivasa Gopal (Journal of Aquatic Food Product Technology, 2016)

Identification and characterization of Fusarium spp. associated with root rots of field pea in North Dakota - Kishore Chittem; Febina M. Mathew; Matthew Gregoire; Robin S. Lamppa; Yen Wei Chang; Samuel G. Markell; Carl A. Bradley; Tharcisse Barasubiye; Rubella S. Goswami (European Journal of Plant Pathology, 2015)

Amplification of long-period waves in shallow coastal embayments of the Great Lakes - Bogdan Hlevca; Mathew G. Wells; Scott Parker (Environmental Fluid Mechanics, 2015)

First record of coralline lethal orange disease (CLOD) in the Indian Ocean - G. S. Aeby; K. Diraviya Raj; G. Mathews; M. Selva Bharath; J. K. Patterson Edward (Coral Reefs, 2015)

Evaluation of the protective effect of Pterocarpus marsupium on acetic acid-induced ulcerative colitis in rats - Merin Maria Mathew; Nguyen Vinh Han; A. Murugesan; E. Arun Raj; K. G. Prasanth (Inflammopharmacology, 2015)

Empirical and semi-analytical chlorophyll a algorithms for multi-temporal monitoring of New Zealand lakes using Landsat - Mathew G. Allan; David P. Hamilton; Brendan Hicks; Lars Brabyn (Environmental Monitoring and Assessment, 2015)

Linking place-based science to people through spatial narratives of coastal stewardship - J. Silbernagel; G. Host; C. Hagley; D. Hart; R. Axler; R. Fortner; M. Axler; V. Smith; A. Drewes; W. Bartsch; N. Danz; J. Mathews; et al. (Journal of Coastal Conservation, 2015)

Persistence and risk assessment of spiromesifen on tomato in India: a multilocational study - K. K. Sharma; Irani Mukherjee; Balwinder Singh; Kousik Mandal; Sanjay K. Sahoo; Hemanta Banerjee; Tirthankar Banerjee; Sankhajit Roy; Paresh G. Shah; Hemlatta K. Patel; Anil R. Patel; S. Naseema Beevi; et al. (Environmental Monitoring and Assessment, 2014)

Persistence and effect of processing on reduction of fipronil and its metabolites in chilli pepper (Capsicum annum L.) fruits - George Xavier; M. Chandran; Thomas George; S. Naseema Beevi; Thomas Biju Mathew; Ambily Paul; Ranjith Arimboor; V. Vijayasree; G. T. Pradeepkumar; R. Rajith (Environmental Monitoring and Assessment, 2014)

Application of a Three-Dimensional Water Quality Model as a Decision Support Tool for the Management of Land-Use Changes in the Catchment of an Oligotrophic Lake - Dennis Trolle; Bob Spigel; David P. Hamilton; Ned Norton; Donna Sutherland; David Plew; Mathew G. Allan (Environmental Management, 2014)

Population pharmacokinetics of intravenous acetaminophen and its metabolites in major surgical patients - Katie H. Owens; Philip G. M. Murphy; Natalie J. Medlicott; Julia Kennedy; Mathew Zacharias; Neil Curran; Sree Sreebhavan; Mark Thompson-Fawcett; David M. Reith (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Persistent weak thermal stratification inhibits mixing in the epilimnion of north-temperate Lake Opeongo, Canada - Patricia Pernica; Mathew G. Wells; Sally MacIntyre (Aquatic Sciences, 2014)

Consumers and establishment limitations contribute more than competitive interactions in sustaining dominance of the exotic herb garlic mustard in a Wisconsin, USA forest - Mathew E. Dornbush; Philip G. Hahn (Biological Invasions, 2013)

Genetic Diversity in Exon 2 of the Major Histocompatibility Complex Class II DQB1 Locus in Nigerian Goats - Abdulmojeed Yakubu; Adebowale E. Salako; Marcos De Donato; Michael I. Takeet; Sunday O. Peters; Mufliat A. Adefenwa; Moses Okpeku; Mathew Wheto; Brilliant O. Agaviezor; Timothy M. Sanni; Oyeyemi O. Ajayi; Gbolabo O. Onasanya; et al. (Biochemical Genetics, 2013)

Predation inhibits the positive effect of dispersal on intraspecific and interspecific synchrony in pond metacommunities - Jennifer G. Howeth; Mathew A. Leibold (Ecology, 2013)
Recent interest in the ecological drivers of compensatory and synchronous population dynamics has provided an improved yet incomplete understanding of local and regional population oscillations in response to variable environments. Here, we evaluate the effect of dispersal rate and spatiotemporal heterogeneity in predation by the selective planktivore, bluegill sunfish ( Lepomis macrochirus ), on local and regional dynamics of zooplankton in pond metacommunities. A metacommunity consisted of three pond mesocosm communities, one with constant presence of predators, one without predators, and one with alternating presence–absence of predators. The three communities were connected at either no, low (0.7% per day), or high (20% per day) planktonic dispersal. Results demonstrate that heterogeneous predation (1) prevents spatial synchrony among prey populations across local communities, (2) disrupts the synchronous population dynamics within communities produced by dispersal, and (3) induces local compensatory dynamics between species within communities regardless of dispersal rate. Taken together, the results emphasize that spatiotemporal heterogeneity in selective predation can inhibit both intraspecific and interspecific synchrony in metacommunities.

Hindcasting water clarity from Landsat satellite images of unmonitored shallow lakes in the Waikato region, New Zealand - Brendan J. Hicks; Glen A. Stichbury; Lars K. Brabyn; Mathew G. Allan; Salman Ashraf (Environmental Monitoring and Assessment, 2013)

UV-Visible Photoluminescence of TiO2 Nanoparticles Prepared by Hydrothermal Method - S. Mathew; Amit kumar Prasad; Thomas Benoy; P. P. Rakesh; Misha Hari; T. M Libish; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2012)

Complete genome sequencing and evolutionary analysis of dengue virus serotype 1 isolates from an outbreak in Kerala, South India - M. Anoop; Ashish J. Mathew; B. Jayakumar; Aneesh Issac; Sajith Nair; Rachy Abraham; M. G. Anupriya; E. Sreekumar (Virus Genes, 2012)

Global patterns in the impact of marine herbivores on benthic primary producers - Alistair G. B. Poore; Alexandra H. Campbell; Ross A. Coleman; Graham J. Edgar; Veijo Jormalainen; Pamela L. Reynolds; Erik E. Sotka; John J. Stachowicz; Richard B. Taylor; Mathew A. Vanderklift; J. Emmett Duffy (Ecology Letters, 2012)
Despite the importance of consumers in structuring communities, and the widespread assumption that consumption is strongest at low latitudes, empirical tests for global scale patterns in the magnitude of consumer impacts are limited. In marine systems, the long tradition of experimentally excluding herbivores in their natural environments allows consumer impacts to be quantified on global scales using consistent methodology. We present a quantitative synthesis of 613 marine herbivore exclusion experiments to test the influence of consumer traits, producer traits and the environment on the strength of herbivore impacts on benthic producers. Across the globe, marine herbivores profoundly reduced producer abundance (by 68% on average), with strongest effects in rocky intertidal habitats and the weakest effects on habitats dominated by vascular plants. Unexpectedly, we found little or no influence of latitude or mean annual water temperature. Instead, herbivore impacts differed most consistently among producer taxonomic and morphological groups. Our results show that grazing impacts on plant abundance are better predicted by producer traits than by large‐scale variation in habitat or mean temperature, and that there is a previously unrecognised degree of phylogenetic conservatism in producer susceptibility to consumption.

Exotic consumers interact with exotic plants to mediate native plant survival in a Midwestern forest herb layer - Philip G. Hahn; Mathew E. Dornbush (Biological Invasions, 2012)

Radiative forcing of natural forest disturbances - Thomas L. O'Halloran; Beverly E. Law; Michael L. Goulden; Zhuosen Wang; Jordan G. Barr; Crystal Schaaf; Mathew Brown; José D. Fuentes; Mathias Göckede; Andrew Black; Vic Engel (Global Change Biology, 2012)
Forest disturbances are major sources of carbon dioxide to the atmosphere, and therefore impact global climate. Biogeophysical attributes, such as surface albedo (reflectivity), further control the climate‐regulating properties of forests. Using both tower‐based and remotely sensed data sets, we show that natural disturbances from wildfire, beetle outbreaks, and hurricane wind throw can significantly alter surface albedo, and the associated radiative forcing either offsets or enhances the CO 2 forcing caused by reducing ecosystem carbon sequestration over multiple years. In the examined cases, the radiative forcing from albedo change is on the same order of magnitude as the CO 2 forcing. The net radiative forcing resulting from these two factors leads to a local heating effect in a hurricane‐damaged mangrove forest in the subtropics, and a cooling effect following wildfire and mountain pine beetle attack in boreal forests with winter snow. Although natural forest disturbances currently represent less than half of gross forest cover loss, that area will probably increase in the future under climate change, making it imperative to represent these processes accurately in global climate models.

Influence of accurate and inaccurate ‘split-time’ feedback upon 10-mile time trial cycling performance - Mathew G. Wilson; Andy M. Lane; Chris J. Beedie; Abdulaziz Farooq (European Journal of Applied Physiology, 2012)

Shifting of Fluorescence Peak in CdS Nanoparticles by Excitation Wavelength Change - S. Mathew; Santhi Ani Joseph; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2011)

Spurious polyadenylation of Norovirus Narita 104 capsid protein mRNA in transgenic plants - Lolita G. Mathew; Bryan Maloney; Naokazu Takeda; Hugh S. Mason (Plant Molecular Biology, 2011)

Plasma membrane ferric reductase activity of iron-limited algal cells is inhibited by ferric chelators - Mathew B. Sonier; Harold G. Weger (BioMetals, 2010)

Species dispersal rates alter diversity and ecosystem stability in pond metacommunities - Jennifer G. Howeth; Mathew A. Leibold (Ecology, 2010)
Metacommunity theory suggests that relationships between diversity and ecosystem stability can be determined by the rate of species dispersal among local communities. The predicted relationships, however, may depend upon the relative strength of local environmental processes and disturbance. Here we evaluate the role of dispersal frequency and local predation perturbations in affecting patterns of diversity and stability in pond plankton metacommunities. Pond metacommunities were composed of three mesocosm communities: one of the three communities maintained constant “press” predation from a selective predator, bluegill sunfish ( Lepomis macrochirus ); the second community maintained “press” conditions without predation; and the third community experienced recurrent “pulsed” predation from bluegill sunfish. The triads of pond communities were connected at either no, low (0.7%/d), or high (20%/d) planktonic dispersal. Richness and composition of zooplankton and stability of plankton biomass and ecosystem productivity were measured at local and regional spatial scales. Dispersal significantly affected diversity such that local and regional biotas at the low dispersal rate maintained the greatest number of species. The unimodal local dispersal–diversity relationship was predator‐dependent, however, as selective press predation excluded species regardless of dispersal. Further, there was no effect of dispersal on beta diversity because predation generated local conditions that selected for distinct community assemblages. Spatial and temporal ecosystem stability responded to dispersal frequency but not predation. Low dispersal destabilized the spatial stability of producer biomass but stabilized temporal ecosystem productivity. The results indicate that selective predation can prevent species augmentation from mass effects but has no apparent influence on stability. Dispersal rates, in contrast, can have significant effects on both species diversity and ecosystem stability at multiple spatial scales in metacommunities.

Landslide susceptibility zonation mapping and its validation in part of Garhwal Lesser Himalaya, India, using binary logistic regression analysis and receiver operating characteristic curve method - John Mathew; V. K. Jha; G. S. Rawat (Landslides, 2009)

Short Term Exposure to a Violent Video Game Induces Changes in Frontolimbic Circuitry in Adolescents - Yang Wang; Vincent P. Mathews; Andrew J. Kalnin; Kristine M. Mosier; David W. Dunn; Andrew J. Saykin; William G. Kronenberger (Brain Imaging and Behavior, 2009)

Transcriptome Analyses of Amoebic Gill Disease-affected Atlantic Salmon (Salmo salar) Tissues Reveal Localized Host Gene Suppression - James W. Wynne; Maree G. O’Sullivan; Mathew T. Cook; Glenn Stone; Barbara F. Nowak; David R. Lovell; Nicholas G. Elliott (Marine Biotechnology, 2008)

Planktonic dispersal dampens temporal trophic cascades in pond metacommunities - Jennifer G. Howeth; Mathew A. Leibold (Ecology Letters, 2008)
Trophic cascades, in which changes in predation affect the biomass of lower trophic levels, vary substantially in strength and incidence. Most work to explain this variation has focused on local factors and has ignored larger regional effects. To study how metacommunity dynamics can alter trophic cascades, we constructed mesocosm metacommunities consisting of three pond communities with heterogeneous levels of fish predation and examined how planktonic dispersal rate (5–140% per week) affected biomass partitioning. Two of the three communities differed continually in the occurrence of fish and supported different but constant environments in a ‘spatial trophic cascade,’ while the third community supported temporally variable fish occurrence in a ‘temporal trophic cascade.’ We find that the presence, but the not the magnitude, of dispersal dampens temporal trophic cascades through an increase in grazer biomass. In contrast, dispersal has no effect on the strength of spatial cascades due to strong sorting pressures in the communities with constant presence or absence of fish as top predators.

Application of binary logistic regression analysis and its validation for landslide susceptibility mapping in part of Garhwal Himalaya, India - J. Mathew; V. K. Jha; G. S. Rawat (International Journal of Remote Sensing, 2007)

Hydrography and water masses in the southeastern Arabian Sea during March–June 2003 - S. S. C. Shenoi; D. Shankar; G. S. Michael; J. Kurian; K. K. Varma; M. R. Ramesh Kumar; A. M. Almeida; A. S. Unnikrishnan; W. Fernandes; N. Barreto; C. Gnanaseelan; R. Mathew; et al. (Journal of Earth System Science, 2005)

Effect of time and mode of application of potassium on the growth, yield and quality of sugarcane ratoon - Thomas Mathew; T. M. Kurian; Babu George; Sosamma Cherian; Jessy M. Kuriakose; K. Sreekumar; G. Jayakumar (Sugar Tech, 2004)

Residual effects of sulphur nutrition on the ratoon crop of sugarcane - Thomas Mathew; T. M. Kurian; Sosamma Cherian; G. Jayakumar (Sugar Tech, 2003)

Stratification by CARD15 variant genotype in a genome-wide search for inflammatory bowel disease susceptibility loci - Sarah H. Shaw; Jochen Hampe; Ray White; Christopher G. Mathew; Mark E. Curran; Stefan Schreiber (Human Genetics, 2003)

The Control of Biological Invasions in the World's Oceans - N. Bax; J. T. Carlton; A. Mathews‐Amos; R. L. Haedrich; F. G. Howarth; J. E. Purcell; A. Rieser; A. Gray (Conservation Biology, 2001)
The introduction of alien, or nonindigenous, animals and plants has been identified by scientists and policy makers as a major threat to biodiversity in marine ecosystems. Although government agencies have struggled to control alien species on land and freshwater for decades with mixed success, the control of alien marine species is in its infancy. Prevention of introduction and establishment must be the first priority, but many populations of alien marine species are already well established worldwide. National and international policies leave loopholes for additional invasions to occur and provide only general guidance on how to control alien species once they are established. To address this issue, a multinational group of 25 scientists and attorneys convened in 1998 to examine options for controlling established populations of alien marine species. The discussions resulted in a framework for control of alien marine species to provide decision‐making guidance to policymakers, managers, scientists, and other stakeholders. The framework consists of seven basic steps: (1) establish the nature and magnitude of the problem, (2) set objectives, (3) consider the full range of alternatives, (4) determine risk, (5) reduce risk, (6) assess benefits versus risks, and ( 7) monitor the situation. This framework can provide guidance for control efforts under the existing patchwork of national laws and can help provide a foundation for international cooperation.

The Control of Biological Invasions in the World's Oceans - N. Bax; J. T. Carlton; A. Mathews-Amos; R. L. Haedrich; F. G. Howarth; J. E. Purcell; A. Rieser; A. Gray (Conservation Biology, 2001)

Mitochondrial phylogeography, subspecific taxonomy, and conservation genetics of sandhill cranes (Grus canadensis; Aves: Gruidae) - Judith M. Phymer; Mathew G. Fain; Jane E. Austin; Douglas H. Johnson; Carey Krajewski (Conservation Genetics, 2001)

Analysis of single-nucleotide polymorphisms in the interleukin-4 receptor gene for association with inflammatory bowel disease - M. Olavesen; J. Hampe; M. M. Mirza; R. Saiz; C. M. Lewis; S. Bridger; D. Teare; D. F. Easton; T. Herrmann; G. Scott; J. Hirst; J. Sanderson; et al. (Immunogenetics, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

An Ecology‐Based Method for Defining Priorities for Large Mammal Conservation: The Tiger as Case Study - Eric D. Wikramanayake; Eric Dinerstein; John G. Robinson; Ullas Karanth; Alan Rabinowitz; David Olson; Thomas Mathew; Prashant Hedao; Melissa Conner; Ginette Hemley; Dorene Bolze (Conservation Biology, 1998)
The disappearance of large vertebrates in the tropical belt may be the next biological insult of the global extinction crisis. Large predators and their prey are at particular risk in Asia, where they are threatened by poaching and habitat loss. To facilitate the best use of limited conservation resources, we created an objective, ecology‐based method for identifying priority areas for conservation that incorporates both habitat representation and landscape‐level features. Using tigers as an example, our method captures the range of ecological habitats where they occur, accounting for ecological, demographic, genetic, and behavioral differences. Our analysis is hierarchical. We divided the tiger range into distinct bioregions and identified tiger habitat types within each. We then delineated tiger conservation units throughout the bioregions and ranked the units based on habitat integrity, poaching pressure, and tiger population trends. To maintain representation of tiger populations and their ecology in the different tiger habitats, we made comparisons only among tiger conservation units from the same tiger habitat types nested within the same bioregion. We identified 159 tiger conservation units in three bioregions—the Indian subcontinent, Indochina, and Southeast Asia. We ranked the units in three categories that reflect the probability of long‐term persistence of tiger populations ( highest in level I units). Twenty‐five tiger conservation units were classified as level I, 21 as level II, and 97 as level III. An additional 16 tiger conservation units for which little information is available were identified for immediate surveys. Levels I , II, and those identified for immediate surveys are the priority areas for immediate funding and for a regional tiger conservation strategy. One feature emerging from the study showed that protected areas cover only small areas of tiger conservation units. If the long‐term prospects for tiger conservation are to improve, poaching must be stopped and protected areas increased in number, linked, and buffered by natural habitats. To enhance landscape integrity, the priority tiger conservation units that straddle international borders should be managed as transboundary reserves, giving tiger conservation a stronger regional structure. Like tigers, populations of other wide‐ranging mammalian carnivores and large herbivores also are declining due to poaching and loss of habitat. The method we present for tigers can be adapted readily to improve conservation strategies for these species as well. Método con Bases Ecológicas para Definir Prioridades para la Conservación de Mamíferos Mayores: El Tigre como Caso de Estudio La desaparición de vertebrados grandes en el cinturón tropical podría ser el siguiente insulto biológico de la crisis de exteinción global. Los depredadores grandes y sus presas se encuentran en un riesgo particular en Asia donde la caza furtiva y la pérdida de hábitats los amenaza. Para facilitar el mejor uso de los limitados recursos de conservación, hemos creado un método objetivo con bases ecológicas que incorpora tanto la representación del hábitat, como las características a nivel de paisaje en la identificación de áreas prioritarias para conservación. Utilizando tigres como ejemplo, nuestro método captura el rango de hábitats ecológicos donde los tigres pueden estar presentes tomando en cuenta diferencias ecológicas, demográficas, genéticas y de conducta. Nuestro análisis es jerárquico. Dividimos el rango de los tigres en bioregiones distintas e identificamos tipos de hábitat para tigres dentro de estas regiones. Posteriormente delineamos unidades de conservación de tigres a lo largo de las bioregiones y organizamos por rangos las unidades en base a la integridad del hábitat, presión por caza furtiva y tendencias de las poblaciones de tigres. Para mantener la representación de las poblaciones de tigres y su ecología en los diferentes hábitats, únicamente hicimos comparaciones entre unidades de conservación de tigres del mismo tipo de hábitat para tigres, anidados dentro de una misma bioregión. Identificamos 159 unidades de conservación de tigres en tres bioregiones—el subcontinente Indú, Indochina y Sur de Asia. Organizamos por rangos las unidades en tres categorías que reflejan la probabilidad de persistencia a largo plazo de poblaciones de tigres (los mayores en unidades de nivel I). Veinticinco unidades de conservación de tigres fueron clasificadas como nivel I, 21 como nivel II y 97 como nivel III. Dieciséis unidades de conservación de tigres adicionales con poca información viable fueron identificadas para muestreo inmediato. Los niveles I y II y aquellos identificados como muestreos inmediatos son áreas prioritarias para financiamiento immediato y para una estrategia de conservación de tigres. Una característica emergente en el estudio muestra que áreas protegidas cubren únicamente áreas pequeñas de unidades de conservación de tigres. Si las perspectivas a largo plazo para la conservación de tigres van a mejorar, la caza ilegal debe ser detenida y las áreas protegidas incrementadas en número, ligadas y amortiguadas por hábitats naturales. Para mejorar la integridad del paisaje, las unidades prioritarias de conservación de tigres que presentan fronteras internacionales deberán ser manejadas como reservas transfronterizas otorgándole a la conservación de tigres una etsructura regional mas fuerte. Así como los tigres, poblaciones de otros carnívoros de amplio rango y herbívoros grandes estan en disminución debido a la caza furtiva y la pérdida del hábitat. El método que presentamos para tigres puede ser adaptado fácilmente para mejorar también las estrategias de conservación de estas especies.

An Ecology-Based Method for Defining Priorities for Large Mammal Conservation: The Tiger as Case Study - Eric D. Wikramanayake; Eric Dinerstein; John G. Robinson; Ullas Karanth; Alan Rabinowitz; David Olson; Thomas Mathew; Prashant Hedao; Melissa Conner; Ginette Hemley; Dorene Bolze (Conservation Biology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Measurement of Void Size Correlation in Inhomogeneous Porous Media - Toby Mathews; G. Peter. Matthews; Cathy J. Ridgway; Adam. K. Moss (Transport in Porous Media, 1997)

Nucleotide and deduced amino acid sequence of the 3? end of the BYMV-MI genome - A. Mathews; G. Dwyer; S. Wylie; M. G. K. Jones (Archives of Virology, 1995)